PENGARUH MODEL TEAMS GAMES TOURNAMENT TERHADAP HASIL PEMBELAJARAN IPS DI KELAS V SD - Ramayani, Mega Leza; Lubis, Mansur; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this research is to find out about the significant effect on the use of the teams games tournament (TGT) cooperative learning technique on the learning result of Social Science subject of 5th Grade student of Bandar Buat Padang Elementary School No.10. The type of research used is quasi-experiment using the design of non-equivalent control group design. The sample of this study were student of the 5th grader in 5A and 5B class of Bandar Buat Padang  Elementary School No.10. The sampling technique used was saturated sampling. At the 5% significance level, the analysis result of the hypothesis test have obtained that tcalculation > ttable (2.73 > 1.67). Based on the study result, it is concluded that there is a significant effect on the use of the TGT cooperative learning technique on the student learning in the social science subject.  Keywords: Teams Games Tournament, learning result, social science